2011
DOI: 10.1177/1756283x11415892
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ion channels for the treatment of gastrointestinal motility disorders

Abstract: Gastrointestinal (GI) functional and motility disorders are highly prevalent and responsible for long-term morbidity and sometimes mortality in the affected patients. It is estimated that one in three persons has a GI functional or motility disorder. However, diagnosis and treatment of these widespread conditions remains challenging. This partly stems from the multisystem pathophysiology, including processing abnormalities in the central and peripheral (enteric) nervous systems and motor dysfunction in the GI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 144 publications
(213 reference statements)
0
50
0
Order By: Relevance
“…The pacemaking mechanisms of small intestinal ICCs are coupled with IP 3 -dependent Ca 2 þ release from endoplasmic reticulum and the activation of pacemaker channels. Transient receptor potential (TRP) channels, Ca 2 þ -activated Cl À channels, are candidates for pacemaker potentials (Nakayama et al, 2007;Beyder and Farrugia, 2012;Zhu et al, 2009). Recently, we reported that hyperpolarization-activated cyclic nucleotide (HCN) channels are also involved in generating pacemaker potentials in colonic ICCs, and act as possible pacemaker channels (Shahi et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…The pacemaking mechanisms of small intestinal ICCs are coupled with IP 3 -dependent Ca 2 þ release from endoplasmic reticulum and the activation of pacemaker channels. Transient receptor potential (TRP) channels, Ca 2 þ -activated Cl À channels, are candidates for pacemaker potentials (Nakayama et al, 2007;Beyder and Farrugia, 2012;Zhu et al, 2009). Recently, we reported that hyperpolarization-activated cyclic nucleotide (HCN) channels are also involved in generating pacemaker potentials in colonic ICCs, and act as possible pacemaker channels (Shahi et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping supports this notion, but specific impact of individual genes remains unclear. 5 Ion channels are excellent pathophysiologic and therapeutic targets because they are directly involved in both GI motility 6, 7 and visceral pain. 8 Therefore, ion channelopathies may cause IBS in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…Functional GI disorders (FGIDs) are complex multisystem pathologies that involve abnormalities in GI secretion, motility, sensation, and central perception. Abdominal pain is a common and prominent feature of FGIDs . The role of ion channels in the transmission of visceral sensation is well established at mucosal, smooth muscular, and neuronal level .…”
Section: Introductionmentioning
confidence: 99%